Egg Hatchability of Various Superior Chicken Strains in Kendari City - Al Jumiati, Wa Ode; Nafiu, La Ode; Saili, Takdir (Pascasarjana Universitas Halu Oleo, 2024)
This research aims to analyze the egg hatchability of several superior chicken strains in Kendari City conducted from February to March 2023. The research materials included eggs from five superior chicken strains, namely Balitnak Improved Village Chicken (KUB), Sensi Chicken, ULU Chicken, Arab Silver (AS), and Kampung Chicken (AK), totaling 300 eggs (60 eggs from each strain). Each treatment consisted of 5 replications, resulting in 25 experimental units. Each unit had 12 eggs and followed a Completely Randomized Design (CRD). The study found that the chicken strain significantly influenced (P